2021
DOI: 10.3390/ani11113201
|View full text |Cite
|
Sign up to set email alerts
|

An Official Outbreak Investigation of Acute Haemorrhagic Diarrhoea in Dogs in Norway Points to Providencia alcalifaciens as a Likely Cause

Abstract: An outbreak investigation was initiated in September 2019, following a notification to the Norwegian Food Safety Authority (NFSA) of an unusually high number of dogs with acute haemorrhagic diarrhoea (AHD) in Oslo. Diagnostic testing by reporting veterinarians had not detected a cause. The official investigation sought to identify a possible common cause, the extent of the outbreak and prevent spread. Epidemiological data were collected through a survey to veterinarians and interviews with dog owners. Diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…2 weeks after the video scoring, the students applied their QBA skills by scoring during direct observations of dogs in a local shelter. However, the shelter was subsequently closed for intake of new dogs due to an outbreak of acute haemorrhagic diarrhoea of dogs in Norway [14]. For biosecurity reasons, the scoring sessions could therefore not continue.…”
Section: Resultsmentioning
confidence: 99%
“…2 weeks after the video scoring, the students applied their QBA skills by scoring during direct observations of dogs in a local shelter. However, the shelter was subsequently closed for intake of new dogs due to an outbreak of acute haemorrhagic diarrhoea of dogs in Norway [14]. For biosecurity reasons, the scoring sessions could therefore not continue.…”
Section: Resultsmentioning
confidence: 99%
“…Providencia alcalifaciens has been associated with a recent outbreak of AHDS in Norway affecting over 50 dogs with a significant number of deaths (Jorgensen and others 2021). Previously, it had only been reported very rarely (Mohr and others 2002).…”
Section: Putative Causesmentioning
confidence: 99%
“…In the autumn of 2019, there was an outbreak of acute hemorrhagic diarrhea syndrome in dogs in Norway. Providencia alcalifaciens was identified as a possible cause of the outbreak ( 1 ). To determine whether P. alcalifaciens could stem from a common source, isolates from diseased dogs were sequenced.…”
Section: Announcementmentioning
confidence: 99%
“…To determine whether P. alcalifaciens could stem from a common source, isolates from diseased dogs were sequenced. Phylogenetic analysis revealed that several isolates clustered closely together, thus suggesting a common origin ( 1 ). P. alcalifaciens has previously been associated with cases of enteritis in dogs ( 2 , 3 ), but a possible role of this pathogen in causing acute hemorrhagic diarrhea in dogs is not well documented.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation